2008
DOI: 10.1002/hrdq.1232
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of leadership effectiveness: Implementing change and driving innovation in organizations

Abstract: Research indicates that numerous variables impact a leader's effectiveness. In this study, the authors explore leadership effectiveness in driving change and innovation, along with the precursory skills necessary to do so. The findings confirm previously identified low rates of organizational success with change and point to skill deficiencies as a cause. Specifically, the abilities to communicate appropriately and motivate others significantly influence a leader's ability to effectively implement change and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 34 publications
3
79
0
6
Order By: Relevance
“…Several attempts have been made in the recent past to identify contextual variables that might help to alleviate the negative effects of resistance to change, with most studies stressing the crucial role played by situational factors such as participation in the change process (Sagie and Koslowsky 1996;Wanberg and Banas 2000), level and quality of change communication (Hargie and Tourish 1996;DiFonzo and Bordia 1998;Bordia, Hunt, Paulsen, Tourish and DiFonzo 2004;Gilley, Dixon and Gilley 2008), rewards (Oreg 2006), quality of relationships with leaders (Goltz and Hietapelto 2002;Furst and Cable 2008;Van Dam, Oreg and Schyns 2008;Levay 2010) and change in leadership strategies (Geller 2002;Szabla 2007). For example, Oreg and Berson (2011) have recently shown that the relationship between employees' dispositional resistance to change and resistance intentions was moderated by transformational leadership such that individuals who were high in resistance to change exhibited lower levels of resistance intentions when transformational leadership was high.…”
Section: The Moderating Role Of Innovative Work Behaviormentioning
confidence: 99%
“…Several attempts have been made in the recent past to identify contextual variables that might help to alleviate the negative effects of resistance to change, with most studies stressing the crucial role played by situational factors such as participation in the change process (Sagie and Koslowsky 1996;Wanberg and Banas 2000), level and quality of change communication (Hargie and Tourish 1996;DiFonzo and Bordia 1998;Bordia, Hunt, Paulsen, Tourish and DiFonzo 2004;Gilley, Dixon and Gilley 2008), rewards (Oreg 2006), quality of relationships with leaders (Goltz and Hietapelto 2002;Furst and Cable 2008;Van Dam, Oreg and Schyns 2008;Levay 2010) and change in leadership strategies (Geller 2002;Szabla 2007). For example, Oreg and Berson (2011) have recently shown that the relationship between employees' dispositional resistance to change and resistance intentions was moderated by transformational leadership such that individuals who were high in resistance to change exhibited lower levels of resistance intentions when transformational leadership was high.…”
Section: The Moderating Role Of Innovative Work Behaviormentioning
confidence: 99%
“…In addition, these leaders must willingly accept criticism, maintain a sense of humor, allow others to offer suggestions and recommendations, and be accepting of employees' successes and failures (Gilley et al, 2008).…”
Section: Characteristics Of Developmental Leadershipmentioning
confidence: 99%
“…При этом развитие талантов важно для ор-ганизации с точки зрения как удержания персонала, так и подготовки работников для реализации стратегических задач ком-пании и формирования ключевых компе-тенций [Gilley, Dixon, Gilley, 2008]. Оценка эффективности системы развития также является весьма важной [Berke, Kossler, Wakefield, 2009;Clarke, 2012], но тем не менее исследователи не делают однознач-ного вывода о том, как правильно оцени-вать результаты системы развития талант-ливых сотрудников [Collings, Anthony, Scul li on, 2009].…”
Section: развитие талантливых сотрудников как практика управления: поunclassified